Presuppositions in Joji’s Selected Song Lyrics - Ginting, Bernardus Batara Tuahta Praditya; Panggabean, Himpun; Silalahi, Charles David Marudut (Jurnal Pendidikan Impola, 2024)
The study analyzes types of presupposition in Joji’s song lyrics. The study's objective is to find the types of presuppositions in Joji’s song lyrics in Joji’s song lyrics. The study uses the descriptive qualitative method with an interactive model data analysis by Miles et al (2014). The data were taken from the verified song lyrics platform, Genius.com®. There are 16 data sources from different albums taken and the total of data found are 65 presuppositions. The analysis showed that only five types of presuppositions were found in the selected song lyrics, which are existential presuppositions (34%), structural presuppositions (25%), factive presuppositions (21%), Counterfactual presuppositions (12%), and lexical presuppositions (8%). The most dominant type of presupposition found in JOJI’s selected song lyrics is existential presupposition with 22 occurrences and the least type of presupposition used in the selected song lyrics is the lexical presupposition with 5 occurrences. The singer more tends to explain about the presence of other entities in the found presumptions from his songs.